Optimized Simulation Framework for Spiking Neural Networks using GPU's - MIRSU, R.; MICUT, S.; CALEANU, C.; MIRSU, D. B. (Advances in Electrical and Computer Engineering, 2012)
This paper presents a hardware accelerated model of a spiking neural network implemented in CUDA C. It does a short description of the mathematical model for the neural network and presents the implementation on the GPU. Additionally, it presents three methods of further accelerating the model by eliminating excess kernel launch overhead time, efficiently using shared memory and overlapping computation with data transfer. Finally, the implementation is benchmarked against an existing C++ equivalent model.